Food restriction alters salivary cortisol and a-amylase responses to a simulated weightlifting competition without significant performance modification - Durguerian, A.; Filaire, E.; Drogou, C.; Bougard, C.; Chennaoui, M. (Journal of Sports Sciences, 2018)
The aim of this investigation was to evaluate the effect of a 6-day food restriction period on the physiological responses and performance of 11 high-level weightlifters. After a period of weight maintenance (T2), they were assigned into two groups depending on whether they lost (Diet group, n = 6) or maintained their body weight (Control group, n = 5) during the course of those 6 days. An evaluation of performance and the measurement of salivary cortisol concentrations and salivary a-amylase (sAA) activity were performed during a simulated weightlifting competition which took place at T2, after a 6-day period of food restriction (T3). Dietary data were collected using a 6-day diet record. We noted a 41.8% decrease in mean energy intake during the dietary restriction period, leading to a 4.34% weight loss for the Diet group. Dietary restriction did not modify absolute performance levels, whilst a significant improvement was noted for the Control group. Furthermore, we noted a response of decreased salivary cortisol and increased sAA activity to the simulated competition stress at T3 for the Diet group. These results may indicate that dietary reduction led to a dissociation of the hypothalamo-pituitary-adrenal axis and the sympatho-adreno-medullary system, which could impair training adaptations and absolute performance development.